LASERPUNCTURE TO IMPROVE THE QUALITY OF LIFE BURJA GOATS AFTER FOOT AND MOUTH DISEASE: LASERPUNKTUR UNTUK MENINGKATKAN KUALITAS HIDUP KAMBING BURJA PASCA MENDERITA PENYAKIT MULUT-KUKU - Miyayu Soneta Sofyan; Siti Eliana Rochmi; Dony Chrismanto (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: The Foot and Mouth Disease (FMD) pandemic that hit throughout 2021-2022 had an impact on the decline in health and weight loss of livestock farmers in Lawang who are members of the Burja Goat Edu Farm by more than 50%. Objective: Knowing the benefits of giving routine Laser Puncture to the Burja Goat acupuncture points to increase their weight and health status. Method: Observation and administration of Laserpuncture on 20 goats in one observation pen. The use of Laser puncture to increase body weight in Burja goats is carried out periodically for 2 months with frequency of twice a week. Observating, counseling, and recording of weight gain and health status of Burja goats. Results: Observation and recording of the provision of Laserpuncture showed an increase in body weight of 0.5 kg per week in 1 month it could reach 4 kg. Counseling, coaching and mentoring from students were carried out to record the health status of burja goats by routinely providing vitamins according to the dosage needed at each stage of their growth and development. Conclusion: Laserpuncture administration on Burja goats provides an increase in body weight of 1 kg in 2 weeks and health quality of Burja goats.